The de Sitter invariant special relativity: some physicals implications - Salcedo, Adriana Victoria Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Due to the existence of an invariant length at the Planck scale, Einstein special relativity breaks down at that scale. A possible solution to this problem is arguably to replace the Poincare-invariant Einstein special relativity by a de Sitter invariant special relativity. Such replacement produces concomitant changes in all relativistic theories, including of course general relativity, which changes to what is called de Sitter modified general relativity, whose gravitational field equation is the de Sitter modified Einstein equation. A crucial property of this theory is that both the background de Sitter curvature and the gravitational dynamical curvature turns out to be included in the same curvature tensor. This means that the cosmological term Λ no longer explicitly appears in Einstein equation, and is consequently not restricted to be constant. In the first part of the thesis, a new definition for black hole entropy is defined. This new notion of entropy is strongly attached to the local symmetry, given the fact to be composed of two parts: the usual translational-related entropy plus an additional piece related to the proper conformal transformation. Also, it is obtained the de Sitter modified Schwarzschild solution, and using this solution we explore the consequences for the definition of entropy, as well as for the thermodynamics of the Schwarzschild-de Sitter system. In the second part the Newtonian limit of the de Sitter modified Einstein equation is obtained, and the ensuing Newtonian Friedmann equations are show to provide a good account of the dark energy content of the present-day universe. Finally, by using the same Newtonian limit, the circular velocity of stars around the galactic center is studied. It is shown that the de Sitter modified Newtonian force, which becomes effective only in the Keplerian region of the galaxy, could possibly explain the flat rotation curve of galaxies without necessity of supposing the existence of dark matter.

Devido a existência de um comprimento invariante na escala de Planck, a relatividade especial de Einstein deixa de ser valida naquela escala. Uma solução possível para esse problema é trocar a relatividade especial de Einstein, a qual tem o grupo de Poincaré como grupo de simetria, por uma relatividade especial invariante sob o grupo de de Sitter. Essa troca ira produzir mudanças concomitantes em todas as teorias relativísticas, incluindo naturalmente a teoria da relatividade geral. Essa teoria da origem ao que denominamos de Sitter modified general relativity, cuja equação para o campo gravitacional foi chamada de de Sitter modified Einstein equation. Uma propriedade crucial dessa teoria é que tanto a curvatura de fundo de de Sitter como a curvatura dinâmica da gravitação estão ambas incluídas no mesmo tensor de curvatura. Isso significa que o termo cosmológico Λ não aparece explicitamente na equação de Einstein, e consequentemente não é restrito a ser uma constante. Trabalhando no contexto da de Sitter modified general relativity, na primeira parte da tese, uma nova definição de entropia para buraco negro é definido. Esta nova noção de entropia está fortemente ligado à simetria local, dado o fato de ser composto por duas partes: uma associada as translação e uma parte adicional relacionada com a transformação conformal. Assim mesmo, nós obtemos a solução de Schwarzschild modificada por de Sitter. Usando essa solução exploramos as consequências para a definição de entropia, bem como para a termodinâmica do sistema de Schwarzschild-de Sitter. Na segunda parte da tese obtemos o limite Newtoniano da de Sitter modified Einstein equation, e usamos as correspondentes equações de Friedmann Newtonianas para estudar o problema da energia escura. Mostramos que essas equações fornecem uma solução bastante razoável para a existência de energia escura do universo atual. Finalmente, usamos o mesmo limite Newtoniano para estudar a velocidade circular de estrelas ao redor do núcleo galáctico. Mostramos que a força Newtoniana modificada por de Sitter, a qual torna-se ativa apenas na região Kepleriana da galáxia, pode explicar as curvas de rotação planas sem necessidade de supor a existência de matéria escura.
A relatividade especial de Sitter e algumas implicações fisicas
Keywords: de Sitter invariant special relativity; de Sitter modified gravitational theory; Dark energy problem; Dark matter problem; Relatividade especial de de Sitter; Teoria gravitacional modificada por de Sitter; Problema da energia escura; Problema da materia escura